The Digital Literacy Skill Training for Aliran Kebatinan Perjalanan's Adherence to Verifying Hoax News - Moh Faidol Juddi; Nugroho Catur; Haqqu Rizca (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Information and communication technology advancement has made information dissemination rapid and massive. In addition, technology facilitates the large spread of hoax news which has sparked various kinds of riots in society. Yet, most people are prone to become exposed to hoax news because they tend to take information for granted from the internet without a critical process. This attitude drives them to any hazardous circumstances because hoax news has affected their perception of presuming phenomena in societies. Thus, a series of programs have been conducted, including the Community Service Program (PKM) by lecturers of the Communication Science Studies Program, at Telkom University, which was specifically carried out by providing training to Aliran Kebatinan Perjalanan's adherence in Bandung to verify hoax news and produce digital media positive contents. This training was conducted in two stages, through materials delivered by appointed presenters and two-way one-by-one coaching that is aimed to develop knowledge and solve problems without patronizing. The program was evaluated using a feedback survey. The result showed that the training had significantly answered the participants' needs in dealing with hoax news and producing digital media content responsibly.